Harnessing Artificial Intelligence: Revolutionizing Investment Decision Processes (Journal of Finance, Business and Management Studies, 2024)
This document is about the evolution of investment strategies by AI in financial decisionmaking. Artificial Intelligence (AI) is creating a change in operational activity, decisionmaking process for investment, and assessing clients, by banks. The purpose of the paper is to highlight the opportunities available by AI in investment decision-making along with challenges, which should be addressed during implementation. A systematic literature review is been used to analyze the paper and make findings. Personalized investment advice, tailored to individual risk tolerance and goals, enhances decisionmaking. Overcoming barriers to AI adoption promises growth, innovation, and user-friendly investment experiences.
Keywords: Artificial Intelligence; Investment Decision-Making; Decision Processes; Benefits; Barriers